2004
DOI: 10.1890/03-5268
|View full text |Cite
|
Sign up to set email alerts
|

SOURCES, SINKS, AND THE ZONE OF INFLUENCE OF REFUGES FOR MANAGING INSECT RESISTANCE TO Bt CROPS

Abstract: The refuge strategy is central for delaying insect resistance to transgenic crops that produce Bacillus thuringiensis (Bt) toxins, but determining an effective spatial configuration of refuges has been problematic. We developed a spatially explicit, demographically based method for estimating the zone of influence of refuges, the area over which refuges increase an insect's population density. The method relied on global positioning system (GPS) and geographic information system (GIS) technologies combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 24 publications
1
57
0
Order By: Relevance
“…Recent advances in the use of geographical information systems (GIS), remote sensing, and spatial statistics are revolutionizing the study of landscapes and enabling researchers to test novel hypotheses from a landscape perspective (Carrière et al 2004(Carrière et al , 2006. Such analyses can be used to identify and quantify areas of natural and humanmanaged habitats on a broad spatial scale.…”
Section: Landscape Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in the use of geographical information systems (GIS), remote sensing, and spatial statistics are revolutionizing the study of landscapes and enabling researchers to test novel hypotheses from a landscape perspective (Carrière et al 2004(Carrière et al , 2006. Such analyses can be used to identify and quantify areas of natural and humanmanaged habitats on a broad spatial scale.…”
Section: Landscape Factorsmentioning
confidence: 99%
“…Such analyses can be used to identify and quantify areas of natural and humanmanaged habitats on a broad spatial scale. These data, combined with field observations of arthropod abundance, can allow researchers to determine the role of habitat variability on arthropod density, the ability of arthropods to disperse between habitats, and the spatial scale of these effects (Carrière et al 2004(Carrière et al , 2006. However, such analyses have primarily dealt with the effects of landscape structure on agricultural pests, and only recently have similar tools been applied to study communities of invasive and native IIGP (Gardiner et al 2009a, b).…”
Section: Landscape Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Considering the source/sink concept, cotton in the landscape may act as a net sink for H. armigera, as our previous studies 19 in the same region show high infestation of cotton fields by H. armigera larvae. However, many studies investigating this concept found changes in the source/sink effects 62,63 of a given landscape element through the season and with the landscape scale. 63 In our study, we investigated the effect of landscape context on the immediate abundance of H. armigera and not the dynamics of the population.…”
Section: No Relationships Between the Abundance Of Moths Developed Onmentioning
confidence: 99%
“…Moreover, tests of predictive refuge strategy models are required to determine if the refuge strategy can delay resistance (14). Furthermore, to improve our ability to develop efficient refuge strategies, empirical approaches are necessary to characterize effects of refuges on resistance evolution (7,15).…”
mentioning
confidence: 99%